The PCPT trial - Hamdy, F; Rouprêt, M (2008)
The PCPT trial is the first phase III trial with the principal objective of examining the hypothesis that the use of chemoprevention could prevent the development of prostate cancer. This is a large scale randomised clinical trial comparing finasteride (5-α reductase inhibitor) to placebo. A total of 18,882 men aged 55 years old or above with unremarkable rectal examination and serum PSA below 3 ng/ml were randomised between daily treatment with 5 mg of finasteride or placebo for 7 years. The incidence of prostate cancer diagnosed by biopsy was 24.4% in the placebo group compared to 18.4% in the finasteride group. The incidence of high Gleason grade cancers (7-10) in the finasteride group (6.4%) appeared to be higher than in the placebo group (5.1%) although it was subsequently shown that these results were not significant. Sexual adverse effects were more common in the finasteride group and urinary symptoms were more common in the placebo group than in the finasteride group. The volumes of prostates treated with finasteride were reduced by 24% compared to the placebo arm. It does not therefore appear at present appropriate to give finasteride to prevent the development of prostate cancer until more detailed results are available about the nature of the cancers which may possibly have been detected or avoided. © 2008 Elsevier Masson SAS. All rights reserved.